POTALA KATUROHINYADI KWATHA IN KAPHAJA YAKRIT DALLUDARA (NON-ALCOHOLIC FATTY LIVER DISEASE): A CASE STUDY - Ashok Kumar Panda,; Jayram Hazra, (International Journal of Ayurveda and Pharma Research, 2020)
Non- alcoholic fatty liver disease (NAFLD) is also otherwise termed as Hepatic steatosis and Kaphaja yakrit dalludara in Ayurveda. 34 years male patient, highly educated from a high socio-economic group of Non vegetarian diet habit came to hospital with complain of anorexia, indigestion and distention for three months. The clinical findings revealed that he is slightly obese, hyperglycaemia and dyslipidimia along elevated liver enzymes with fatty liver in USG and Fibro scan. The case was treated with Patolakaturohinyadi Kwatham (PKK) in the dose was 30ml Kasaya with equal quantity of luke warm water twice daily in empty stomach preferable morning and evening for six months. This study proved that PKK can significantly reduced blood sugar, serum Lipids and liver enzymes within three months along with reduction weight and BMI, but change in liver architecture required six months in this therapy. The BARD score and NAFLD score changed to normal after six months of therapy. The patient was kept in observation for further one year without medication and advised to practice yoga, exercise and low carbohydrate and fat diet to study the recurrence of disease. The liver architecture as well as biochemical profile of liver is maintained after one year also. PKK may correct the metabolic dysfunction by increase Agni, digest Ama which helped in the correction of hyperglycaemia and dyslipidaemia. PKK is safe in for six months of use in recommended dose (30ml BID) as there was no adverse sign and symptom observed and no change in biochemical and Haematological profile of Patients.PKK is safe and effective in this case of Kaphaja Yakrit dalludara (NAFLD). It can study further in large population to generated evidence for its efficacy and efficacy in larger group.